Pembelajaran dan Pengetahuan: Studi Mendasari Kemuridan dan Kesaksian Imam - Tony Setyawan, Yohanes (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2018)
During the initial formation to become Catholic priests, seminarians tend to consider the intellectual formation (study) as merely a requirement to be ordained. Intellectual formation is considered necessary because it orients the seminarians towards their call to be good disciples and their sending as witnesses. Jesus Christ begins his ministry by way of building a community of twelve disciples so that they might have great opportunity to learn from their teacher. In due course, the disciples then become witnesses of Christ’s words and deeds, and are sent to proclaim and to realise the Kingdom of God in the world. These models of learning and formation are applied to the priests-to-be in the Church. The initial formation is a time when seminarians literally become disciples by studying the subjects required by the Church. After their ordination, they will take the role of witness by way of participating in Christ’s offices now carried out by the Church.